Development of a Broadly Protective, Self-Adjuvanting Subunit Vaccine to Prevent Infections by Pseudomonas aeruginosa - Das, Sayan; Howlader, Debaki R.; Zheng, Qi; Ratnakaram, Siva Sai Kumar; Whittier, Sean K.; Lu, Ti; Keith, Johnathan D.; Picking, William D.; Birket, Susan E.; Picking, Wendy L. (Frontiers in Immunology, 2020)
Infections caused by the opportunistic pathogen Pseudomonas aeruginosa can be difficult to treat due to innate and acquired antibiotic resistance and this is exacerbated by the emergence of multi-drug resistant strains. Unfortunately, no licensed vaccine yet exists to prevent Pseudomonas infections. Here we describe a novel subunit vaccine that targets the P. aeruginosa type III secretion system (T3SS). This vaccine is based on the novel antigen PaF (Pa Fusion), a fusion of the T3SS needle tip protein, PcrV, and the first of two translocator proteins, PopB. Additionally, PaF is made self-adjuvanting by the N-terminal fusion of the A1 subunit of the mucosal adjuvant double-mutant heat-labile enterotoxin (dmLT). Here we show that this triple fusion, designated L-PaF, can activate dendritic cells in vitro and elicits strong IgG and IgA titers in mice when administered intranasally. This self-adjuvanting vaccine expedites the clearance of P. aeruginosa from the lungs of challenged mice while stimulating host expression of IL-17A, which may be important for generating a protective immune response in humans. L-PaF’s protective capacity was recapitulated in a rat pneumonia model, further supporting the efficacy of this novel fusion vaccine.